DETERMINATION OF SUITABLE OPENING ANGLE OF HYDRAULIC SUPPORT LEGS FOR DESIGNING M46-130mm SELF-PROPELLED ARTILLERY - Phan Hoang Cuong (Journal of Military Science and Technology, 2020)
This paper determines a suitable opening angle of the hydraulic support legs of M46-130 mm self-propelled artillery. It is a combination of M46-130 mm field gun, mounted on KrAZ-255B 6x6 military truck chassis. Based on results of investigating the changes of forces and moments acting on artillery system in static condition when changing the opening angle of hydraulic support legs at critical fire angles, a suitable angle is selected at ψ = 400 and γ = 200. From that angle, this paper shows a table consists of geometric parameters, forces and moments acting on system. The results of this research are the input parameters to calculate, design and optimize structures of self-propelled artillery.